2020
DOI: 10.1186/s12870-019-2187-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association reveals genetic variation of lint yield components under salty field conditions in cotton (Gossypium hirsutum L.)

Abstract: Background: Salinity is one of the most significant environmental factors limiting the productivity of cotton. However, the key genetic components responsible for the reduction in cotton yield in saline-alkali soils are still unclear. Results: Here, we evaluated three main components of lint yield, single boll weight (SBW), lint percentage (LP) and boll number per plant (BNPP), across 316 G. hirsutum accessions under four salt conditions over two years. Phenotypic analysis indicated that LP was unchanged under… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…BN is a major yield component that significantly contributes to the individual plant yield of cotton [ 22 ]. In a previous study, we have also found that BN is the most important factor in cotton fiber yield [ 20 ]. However, the high CV value and low heritability of BN (72.92%) indicate that the trait is greatly influenced by the environment and is difficult to be controlled in genetic improvement.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…BN is a major yield component that significantly contributes to the individual plant yield of cotton [ 22 ]. In a previous study, we have also found that BN is the most important factor in cotton fiber yield [ 20 ]. However, the high CV value and low heritability of BN (72.92%) indicate that the trait is greatly influenced by the environment and is difficult to be controlled in genetic improvement.…”
Section: Discussionmentioning
confidence: 94%
“…It is of great significance to discover QTLs and candidate genes related to yield traits for genetic improvement of cotton to develop high-yielding cultivars. With the release of genome-wide sequence information, lots of QTLs and genes associated with cotton yield traits were identified by GWAS analysis [ 12 , 20 22 ]. Nevertheless, the yield components are complex quantitative traits controlled by multiple genes and affected by environments.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of salt tolerance genes is of key importance for improving cotton yield in salt affected lands [ 24 , 25 ]. Limited number of salt tolerance genes have been identified in cotton as compared to other model plants [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent years, association mapping as an important method for the identification of complex quantitative traits has been widely used in cotton for various traits including salt tolerance [ 35 40 ]. Jia et al [ 21 ] identified 3 simple sequence repeats (SSR) markers significantly associated with the relative survival rate under salt stress through association mapping methods using 323 G. hirsutum germplasms.…”
Section: Discussionmentioning
confidence: 99%